Carbohydrate-electrolyte feedings improve 1 h time trial cycling performance - Jeukendrup, A.; Brouns, F.; Wagenmakers, A. J.; Saris, W. H. (International Journal of Sports Medicine, 1997)
Carbohydrate-electrolyte (CE) feedings have been shown to improve endurance performance at moderate intensities (60-75% VO2max) and or more than 2 h duration. The effects of CE feedings during high intensity exercise (i.e. > or = 80% VO2 max) of shorter duration (approximately 1 h) are less clear. Therefore the purpose of the present study was to investigate the effect of the ingestion of a 7.6% CE solution during exercise on time trial cycling performance of approximately 1 h. This type of performance testing has been shown to be more reproducible (coefficient of variation 3.35%) than the traditional exercise test to exhaustion. On two occasions and in random order nineteen endurance trained cyclists completed an exercise test requiring the accomplishment of a set amount of work as fast as possible (time trial) under strictly standardized conditions. As the start and during the trials they drank in total 14 ml/kg of either a 7.6% CE solution or artificially flavored and colored water (placebo). Time to complete the set amount of work was significantly reduced and thus performance was significantly increase (p < 0.001) with the CE drink by 2.3%. Time to complete the set amount of work was 58.74 +/- 0.52 min with CE and 60.15 +/- 0.65 min with placebo (p < 0.001). Average workload during the time trials was 297.5 +/- 1.4W and 291.0 +/- 10.3 W, respectively. Subjects exercised at 76.4 +/- 0.7% of their maximal work rate (Wmax) with CE and at 74.8% Wmax with placebo (p < 0.001). It was concluded tht also in relative short term (1h) high intensity (75% Wmax) cycling exercise ingestion of a carbohydrate-electrolyte solution compared to placebo improves performance.